Subtotal splenectomy preserving the lower pole in rats: technical, morphological and functional aspects - Paulo,Danilo Nagib Salomão (2006)
PURPOSE: To assess the possibility of preserving the lower pole of the spleen, supplied by the inferior lobar vessels and segmental vessels, or by vessels of the gastrosplenic ligament, in subtotal splenectomy; to study the viability and function of the lower pole of the spleen. METHODS: Thirty-six male Wistar rats were used in this study. Said animals weighed 273-390 g ( 355.2 ± 30.5 g ), and were randomly distributed into three groups. Group 1 comprised ten animals which were submitted to exploratory laparotomy with spleen manipulation (sham operation). Group 2 comprised 16 animals which were submitted to total splenectomy. Group 3 comprised ten animals which were submitted to subtotal splenectomy, preserving the lower pole of the spleen. Blood was collected from all animals before and 90 days after surgery to measure the levels of cholesterol and triglycerides. The animals were sacrificed 90 days after surgery. Spleens and remaining spleens were removed for macroscopic and microscopic examination. RESULTS: Surgery was performed with no complications in all groups. Six animals died in group 2. Spleens of groups 1 and 2, and lower poles of group 3 were macroscopically viable. Apparent white pulp hyperplasia was observed in group 1. In group 3, slight inflammation and capsular fibrosis were observed at the incision site, as well as diffuse hemosiderosis in the red pulp. Average mass of remaining spleen was 35.84% ± 4.31%. No significant difference was observed between preoperative and late postoperative lipid levels in groups 1 and 3 (p > 0.05). Late postoperative lipid levels significantly increased in group 2. CONCLUSIONS: Preservation of the lower pole of the spleen (supplied by gastrosplenic vessels or inferior lobar vessels and segmental vessels) was possible with subtotal splenectomy. The lower pole was macroscopically and microscopically viable in all cases. Subtotal splenectomy preserving the lower pole prevented changes in lipid levels, which were observed in rats submitted to total splenectomy. Plasma lipid levels in rats submitted to subtotal splenectomy were similar to those observed in sham operated rats.